CubicRing: Enabling One-Hop Failure Detection and Recovery for Distributed In-Memory Storage Systems - Guo, Chuanxiong; Xiong, Yongqiang (USENIX NSDI 2015, 2015)
In-memory storage has the beneﬁts of low I/O latency and high I/O throughput. Fast failure recovery is crucial for large-scale in-memory storage systems, bringing network-related challenges including false detection due to transient network problems, trafﬁc congestion during the recovery, and top-of-rack switch failures. This paper presents CubicRing, a distributed structure for cube-based networks which exploits network proximity to restrict failure detection and recovery within the smallest possible one-hop range. We leverage the CubicRing structure to address the aforementioned challenges and design a network-aware in-memory key-value store called MemCube. In a 64-node 10GbE testbed, MemCube recovers 48 GB of data for a single server failure in 3.1 seconds. The 14 recovery servers achieve 123.9 Gb/sec aggregate recovery throughput, which is 88.5% of the ideal aggregate bandwidth.